Lietuvos TSR bibliotekų istorijos 1940–1941 metais tyrinėjimų klausimu - Sinkevičius, Klemensas (Knygotyra, 1980)
In the summer of 1940, in Lithuania, the socialist revolution was wrought and Soviet power was restored. In the short span of time, up to June 22, 1941, when peaceful labour was interrupted by the agression of Hitlerite Germany, the party and state authorities of the Republic accomplished much in the field of reorganization of librarianship, extension of the library network, replenishment of library stocks, etc. Problems concerned with library development in Soviet Lithuania in 1940–1941 have found reflection in general works on the history of the Republic. There are also some articles dealing with the history of libraries. Nevertheless, the history of libraries in this important period, marked by many outstanding events, has not yet become the subject of a monographic study. The archival materials and other documents of this period have not beeb examined profoundly enough. The study of the history, of libraries of the Lithuanian SSR is not merely of local OT regional character. The history of the libraries of the Republic represents an integral part of the general survey of the history of libraries of the USSR in the last pre-war years.